Beyond Common Metal–Metal Bonds, κ3‐Bis(donor)ferrocenyl→Transition‐Metal Interactions. Issue 10 (6th December 2018) - Ringenberg, Mark R.
Abstract: Ligands with 1, 1′‐bis(donor)ferrocene motif are capable of a wide range of binding modes, including the trans chelation mode in which there is a Fe−M interaction (κ 3 ‐D, Fe, D), in the form of a dative Fe→TM bond (TM=transition metal). This Minireview will explore the nature of this Fe–TM interaction thorough select examples as well as how to characterize a Fe→TM dative bond using physical, computational, and spectroscopic techniques. Abstract : Iron interactions : This Minireview covers the topic of κ 3 ‐1, 1′‐bis(donor)ferrocene ligands in which a dative Fe→M bond is present. Physical, computational, and spectroscopic techniques are also discussed.